SUPERVISI AKADEMIK KEPALA MADRASAH ALIYAH SWASTA - Wiffi Herdini; Sinta Agustin (Program Studi Pendidikan Agama Islam, Universitas Majalengka, 2020)
The headmaster of the madrasa attends school four times a week, six educators concurrently in the course of subjects namely history, Indonesian, biology, physical and health education, citizenship education, and physics. This study aims to uncover the planning, implementation, evaluation and follow-up of academic supervision. The method used is descriptive qualitative research method. Data collection techniques are done by interviewing, observing, studying documentation, and copying. The results showed that; first, the planning of academic supervision in Madrasah Aliyah Al-Muthmainnah is more focused on the preparation of learning preparation design documents, educator administration, class visits and preparation of supervision schedules; second, the implementation of academic supervision is carried out according to the schedule that has been prepared by supervising one to two educators every month for one year, the supervision technique used is class visits and talks with individuals; third, evaluation and follow-up of academic supervision, that is, the educator has an A from the aspects of the assessment of the design of the learning preparation, educator administration, and class visits. But the follow up supervision has not been determined by the madrasa head because it is constrained by several internal factors.